Physical Activity among Older People with Chronic Illnesses: A Cross-sectional Study - Abdullah Alkhawaldeh; Asem Abdalrahim; Mohammed ALBashtawy; Mohammad Suliman; Suzan Zamzam; Omar Al Omari; Mohammed Habeeb; Hasan Alkhawaldeh; Khloud Al Dameery (Jordan University of Science and Technology, 2024)
Background: The significance of physical activity in preventing and treating chronic illnesses has long been approved. Still, there is limited studies that focus on the physical activity among older adults with chronic illnesses in Jordan. Aim: This study intended to search the association between physical activity and chronic illnesses among older adults in Jordan. Methods: A cross-sectional study was carried out among 200 older adults aged 60 years and more who live in north of Jordan. The participants’ physical activity level was examined by the International Physical Activity Questionnaire (IPAQ). Analysis of data was completed using SPSS Statistics. Results: About 41% of older adult have sufficient level of physical activity. Gender, level of schooling, smoking, heart condition, diabetes, and multimorbidity were significantly associated with physical activity. While, in the logistic regression, the factors significantly associated with physical activity among the older adults were gender (OR 0.221, 95% CI .096-.507), heart condition (OR .093, 95% CI .011-.760), and diabetes (OR .312, 95% CI .120-.810). Conclusion: This study revealed a low physical activity level among old adult. Development of policies to support a regular level of physical activity for old adult with chronic illnesses, accompanied by intervention programs, must be distinguished for males and females, and must take into consideration characteristics of illness and limitations of old adult.